Routine Intraoperative Inhaled Milrinone and Iloprost Reduces Inotrope Use in Patients Undergoing Cardiac Surgery: A Retrospective Cohort Pilot Study. (August 2020) - Hu, Xiaobo; Li, Xiaoqiang; Boggett, Stuart; Yang, Yang; Chun-Ting, Wang; Anstey, James; Royse, Alistair; Royse, Colin
Abstract : BACKGROUND: Catecholamine inotropes are frequently used after cardiopulmonary bypass (CPB) but may have undesirable effects. The aim was to identify whether the routine use of inhaled pulmonary vasodilators might reduce the requirement for inotrope drugs after cardiac surgery. METHODS: Retrospective cohort study of sequential patients undergoing cardiac surgery at the Royal Melbourne Hospital performed by a single surgeon and anesthesia care team, within 14 months before and after routine implementation of inhaled pulmonary vasodilators, August 2017. Milrinone 4 mg and iloprost 20 µg were inhaled using a vibrating mesh nebulizer (Aerogen) before initiation of CPB and at chest closure. Other aspects of clinical management were unaltered over the time period. Two investigators blinded to each other extracted data from electronic and written medical records. The primary outcome was any use of inotropes in the perioperative period; a Fisher exact test was used to analyze any differences between the 2 groups. Demographic data, hemodynamic data, and use of inotropes and vasopressors were collected from induction of anesthesia to 36 hours postoperative in the intensive care unit (ICU). Hospital and ICU length of stay, cost, and complications were collected. RESULTS: Any use of inotropes was significantly lower with inhaled pulmonary dilators (62.5% vs 86.8%, odds ratio [95% confidence interval CI], 0.253 (0.083–0.764); P = .011), including intraoperative inotrope use (37.5% vs 86.8%, odds ratio [95% CI], 0.091 (0.03–0.275); P < .001). ICU length of stay was significantly lower with inhaled pulmonary dilators (45 hours, interquartile range [IQR], 27–65 vs 50 hours, IQR, 45–74; P = .026). There were no significant differences among major postoperative complications or costs between groups. CONCLUSIONS: Routine use of inhaled milrinone 4 mg and iloprost 20 µg before and after CPB is associated with reduced postoperative inotrope use.